The number of phenology patterns, not species richness, affects the greening season length of freely assembled plant communities. (21st July 2022) - Rheault, Guillaume; Proulx, Raphaël; Robin, Yoann; Lévesque, Esther
Abstract: Questions: Plant greening phenology is a key response trait that drives numerous ecosystem functions such as carbon storage and flowering. Plant communities with a diversity of phenology responses could show a longer greening season due to more complete occupation of the temporal window available for growth. However, it is unclear how species composition and richness affect the phenology of local plant communities. Location: This study was conducted in wetland landscapes of the St. Lawrence River in the province of Québec, Canada (46.07°N; 73.17°W). Methods: We used close‐range digital imagery to monitor the greening phenology and species richness of 20 herbaceous plant communities from 2013 to 2016. We quantified the number of greening phenology patterns observed each year within each plant community using singular value decomposition of close‐range image time series. Results: The number of plant species within plant communities was independent of the number of phenology patterns, or the length of the greening season. However, the number of phenology patterns correlated positively to the greening season length in all four years of monitoring. Conclusions: The relationship between the number of phenology patterns and the greening season length suggests a complementary use of the temporal window available for growth within plant communities. Species richness was a poor indicator of the diversity of phenology responses in wet meadow communities. The absence of a positive relationship between the number of plant species and the diversity of greening phenology patterns, or the length of the greening season, suggests that other descriptors of plant communities are of importance. Species richness is more often than not a weak predictor of the functioning of local plant communities in the wild. Abstract : Using a novel factorization technique, we showed that the number of phenology patterns in wet meadow communities was an important determinant of the greening season length. By contrast, plant species richness was a poor predictor of phenology patterns or greening season length. Time is ripe for biodiversity–ecosystem experiments to test other dimensions of biodiversity that are less species focused.